Risk Factors Incompliance Treatment of Lung Tuberculosis Patient In Kendari City - Asriati, Asriati; Alifariki, La Ode (Jurnal Keperawatan Terapan, 2020)
The aim of this study was to analysis the risk  factors incompliance treatment of TB patient.in Kendari city. The study was a  control case design, with 136 respondents consist of  68  cases and 68 controls .The cases samples were all newly TB patients  aged 15 years old and above who incompliance treatment .The control samples were  all newly TB patients  aged   15 years old and above, who  compliance treatment. The analysis of the data with tabulation system and statistics by the SPSS with odds ratio.  The results of the study indicated  that from three variables assumed  risky to incompliance to take medicine, there were four variables found to have risk of incompliance , i.e., knowledge OR is 5,492,  and activity supervisor to take medicine  OR is 4,166. The conclusion : Knowledge, activity supervisor to take medicine, side effect of the drug and feeling better  were constitute risk factors to incompliance  treatment of TB patient in kendari city